Fabrication of minichannel fractal flow channels by selective laser melting for two-phase flow cooling applications - Leong, Kai Choong (2018)
Fractal design flow channels provide better flow stability and heat dissipation capacity than conventional parallel channel flow channels under flow boiling conditions although they are difficult to fabricate. The Selective Laser Melting (SLM) technique is selected to explore the feasibility of fabricating minichannel fractal flow channels with four various branch levels, denoted as c = 1, 2, 3, 4, using AlSi10Mg, an aluminium alloy metallic powder. The largest inaccuracy of the flow channel diameters was found to be 1.6%. The flow boiling heat transfer performance was also investigated at a mass flux of 900 kg/m²∙s and was found that c = 2 has the highest heat transfer coefficient, being 3.5%, 0.9% and 5.8% higher than c = 1, c = 3 and c = 4. Preliminary studies shown that the higher flow channel designs experienced dryout at lower heat supplied, which hinders heat transfer performance. This trend may show that higher branch levels may not necessarily lead to better thermal performance.